THE FARES ANALYSIS OF PUBLIC TRANSPORTATION (A Case Study Of Bandung City) - MANURUNG (NIM : 25003048); Pembimbing : Prof. Dr. Ir. Ofyar Z. Tamin, MSc; Dr. Ir. Ade Syafr, DESMON
Most of the public transportation users are the lower middle class people, consequently the fares have to accommodate not only the user's Ability To Pay (ATP) and Willingness To Pay (WTP), but also the operator's interest to keep concern a vehicle operates. The purpose of this research is to analyze the fares of public transportation in Bandung city. The analysis concerns the user's ATP/WTP, Basic Production Cost (BPC), the impact of the rise of fuel price at about 29% on 1st April 2005, and the impact of the owner's profit margin at about Rp. 40.000,-/day or 15% of the vehicle's price per year including a minimum rental fee per day. The research were conducted on the 3 routes based on the types of desingated route configuration for public transportation in Bandung city. The first type is radial, in which the CBD is connected with the other centre of activity i.e. route 03 (Abdul Muis-Dago). The second type is grid, in which the route passing through the CBD i.e. route 32 (Cicadas-Elang). The third type is grid, in which the route does not passing trough the CBD i.e. route 06 (Cicaheum-Ledeng). The primary data were obtained from interviewing the users (to get the value of ATP/WTP), interviewing the drivers (to get the vehicle operational data), and on-board survey troughout the operational time (to get the number of passengers). Vehicle Operating Cost (VOC) is analyzed on 2 (two) conditions: ideal and actual. On the ideal condition, VOC is based on the vehicle operating distance (used FSTPT's method). On the actual condition, VOC is based on the data of driver interview. The conclusion is the VOC in the ideal condition is higher than in the actual condition, because in the actual condition sometimes the unusable components are still used by the vehicle, for example the tire. It caused the BPC in the ideal condition is higher than in the actual condition. From the fare analysis can be concluded that it's about 90% user has the ablity and willingness to pay as much as the VOC. The fares that base on the VOC, is less than the actual fares. It means that the operator will get the profit. The rise in price of fuel on 1st April 2005 where is 29%, causes the rise of fares about 8,8% for the actual condition and 7,3% for the ideal condition. Actually, the rental fee is more than minimum rental fee for the ideal and actual condition. If the owner's profit margin at about Rp. 40.000,-/day or 15% of the vehicle's price per year including in the minimum rental fee, the rental fee is higher than the actual rental fee. It means that the actual rental fee give the profit to the owner in the amount of less than Rp. 40.000,-/day.